Innovated formulation of oseltamivir powder for suspension with stability study after reconstitution using a developed ion-pair reversed phase high-performance liquid chromatography method - Kahtan Jassim Hasson (Wolters Kluwer Medknow Publications, 2022)
Oseltamivir is an antiviral neuraminidase inhibitor used for the treatment and prophylaxis of influenza infection with viruses A and B. The mechanism of oseltamivir antiviral activity is by inhibiting the activity of the viral neuraminidase enzyme present on the surface of the virus, which stops viral replication and infectivity. Oral suspensions of oseltamivir phosphate are dispensed orally capsules and suspension. However, the use of oral suspension for pediatric administration is preferable and is prepared as a powder for suspension. The reconstituted suspension degrades rapidly within a few days. The objective of this work is to establish a stable formulation of oseltamivir phosphate as a suspension and to assure the stability conditions for prolonged use after reconstitution in aqueous form. In addition, this required formulation should maintain a high rate of dissolution, which subsequently leads to higher bioavailability. In this study, oseltamivir forms an inclusion complex with the natural and safe polymer hydroxypropyl beta-cyclodextrin, which resembles a host because its structural cavity carries the oseltamivir molecule in the aqueous preparation and provides a protective property against environmental challengers. In addition, a high-performance liquid chromatography (HPLC) stability-indicating method of analysis has been developed using an ion-pair reversed-phase HPLC technique that is validated for precision, accuracy, reproducibility, and specificity for the determination of oseltamivir in suspension. The results of this work show the relatively long shelf life of the reconstituted oseltamivir oral powder for suspension in the new pediatric formulation, and the developed HPLC method was precisely suitable for stability study.